Rhizosphere microbes enhance plant salt tolerance: Toward crop production in saline soil - Liu, Yunpeng; Xun, Weibing; Chen, Lin; Xu, Zhihui; Zhang, Nan; Feng, Haichao; Zhang, Qiang; Zhang, Ruifu (Computational and structural biotechnology journal, 2022)
The world’s population continues to increase and thus requires more food production to take place in nonarable land, such as saline soil; therefore, it is urgent to find solutions to enhance the salinity tolerance of crops. As the second genome of plants, the rhizosphere microbiome plays critical roles in plant fitness under stress conditions. Many beneficial microbes that help plants cope with salinity stress have been identified, highlighting their roles in mitigating salt stress-induced negative effects on plants. However, a comprehensive review of the microbial species that are able to confer plant salt tolerance and the underlying mechanisms is still lacking. In this review, we compared the representative fungal and bacterial taxa that demonstrate the ability to enhance plant growth in saline soil. We also reviewed the mechanisms by which rhizosphere microbes enhance plant salt stress tolerance, i.e., by re-establishing ion and osmotic homeostasis, preventing damage to plant cells, and resuming plant growth under salt stress. Finally, future research efforts to explore the rhizosphere microbiome for agricultural sustainability are proposed.